STUDENTS PERCEPTION OF EDUCATION SERVICES BASED OPTIMIZATION OF GOVERNMENT REGULATION NUMBER 19 OF 2005 - Lady Anst; Berchah Piteoewas; Hermi Yanzi (FKIP Unila, 2012)
The aimed of this research was to explain how students perception the optimization of education services based on Government Regulation 19th 2005 about National Standards of Education in Senior High School YP Unila Bandar Lampung. Method used descriptive. The subject researched was students in Senior High School YP Unila Bandar Lampung in year 2012/ 2013. Samples were 10% or 114 persons. Data were analyzed using percentage formula. Thus it can be concluded that the perception of students toward the optimization of educational services based Government Regulation 19th 2005 about National Standards of Education in Senior High School YP Unila Bandar Lampung have to meet the standards and the services that have been provided school education can understand and function according to the needs of students.Keywords: education services, national standards of education, government regulation